Proteomics and phosphoproteomics of chordoma biopsies reveal alterations in multiple pathways and aberrant kinases activities - Hang, Jing; Ouyang, Hanqiang; Wei, Feng; Zhong, Qihang; Yuan, Wanqiong; Jiang, Liang; Liu, Zhongjun (Frontiers in Oncology, 2022)
Background: Chordoma is a slow-growing but malignant subtype of bone sarcoma with relatively high recurrence rates and high resistance to chemotherapy. It is urgent to understand the underlying regulatory networks to determine more effective potential targets. Phosphorylative regulation is currently regarded as playing a significant role in tumorigenesis, and the use of tyrosine kinase inhibitors in clinical practice has yielded new promise for the treatment of a variety of sarcoma types. Materials and methods: We performed comprehensive proteomic and phosphoproteomic analyses of chordoma using four-dimensional label-free liquid chromatography–tandem mass spectrometry (LC-MS/MS) and bioinformatics analysis. The potential aberrantly expressed kinases and their functions were validated using western blotting and CCK-8 assays. Results: Compared with paired normal muscle tissues, 1,139 differentially expressed proteins (DEPs) and 776 differentially phosphorylated proteins (DPPs) were identified in chordoma tumor tissues. The developmentally significant Wnt-signaling pathway and oxidative phosphorylation were aberrant in chordoma. Moreover, we predicted three kinases (AURA, CDK9, and MOK) with elevated activity by kinase-pathway network analysis (KiPNA) and verified their increased expression levels. The knockdown of these kinases markedly suppressed chordoma cell growth, and this was also the case for cells treated with the CDK9 inhibitor AZD4573. We additionally examined 208 proteins whose expression and phosphorylation levels were synergetically altered. Conclusions: We herein depicted the collective protein profiles of chordomas, providing insight into chordomagenesis and the potential development of new therapeutic targets. Keywords: Chordoma, Proteomics, Phosphoproteomics, Integrated kinase network, Kinase inhibitor